1995
DOI: 10.1136/bjo.79.3.250
|View full text |Cite
|
Sign up to set email alerts
|

Is leprosy blindness avoidable? The effect of disease type, duration, and treatment on eye damage from leprosy in Uganda.

Abstract: Aims-The study was designed to measure the prevalence, range, and severity of eye involvement in leprosy patients; to relate this to disease type, duration, and treatment to identify risk factors; and to provide practical guidelines for programme managers and field staff on the prevention ofblindness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
(2 reference statements)
0
15
0
Order By: Relevance
“…Among 19 Nepali PB patients undergoing cataract surgery, 11 had cellular inflammatory infiltrations in the iris. A survey in Uganda 23 found clinical evidence of chronic uveitis in 16 of 364 (4.4%) patients with PB disease. These cases were generally older and had a longer duration of disease than PB patients without chronic uveitis.…”
Section: Uveal Disease (And Complicated Cataract)mentioning
confidence: 98%
See 1 more Smart Citation
“…Among 19 Nepali PB patients undergoing cataract surgery, 11 had cellular inflammatory infiltrations in the iris. A survey in Uganda 23 found clinical evidence of chronic uveitis in 16 of 364 (4.4%) patients with PB disease. These cases were generally older and had a longer duration of disease than PB patients without chronic uveitis.…”
Section: Uveal Disease (And Complicated Cataract)mentioning
confidence: 98%
“…Data from Uganda showed that leprosy patients with evidence of chronic uveitis have a 3-fold risk (95% CI 1.6, 5.5) of cataract, independent of age. 23 The incidence of acute uveitis in leprosy patients is not known but MB patients during type II reaction are at an increased risk of this. Among 25 Indian patients undergoing type II reaction, only 1 patient had acute uveitis, whereas an additional 2 to 3 patients had subacute uveitis.…”
Section: Uveal Disease (And Complicated Cataract)mentioning
confidence: 99%
“…A similar assessment of cataract surgical coverage among inhabitants of leprosy settlements in Nigeria was 44% (23/52 patients, cutoff point VAo0.05). 12 Reasons for not having had surgery in the Korean study (VAo0.3) were 'cataract not mature' in 28/48 (58%) patients, and 'no felt need' in 9/48 (19%) patients. In Nigeria, the main reasons for not having had surgery were 'costs' in 38/107 (36%), 'no service available' in 26 (24%), 'no felt need' in 19 (18%) (mainly unilateral cataract), 'unawareness of treatment' in 10 (9%), and fear in nine (8%) of patients.…”
Section: Cataractmentioning
confidence: 99%
“…The role of chronic uveitis in unclear, but may triple the risk of cataract. 12 The quoted studies all illustrate the high prevalence of cataract as a cause of blindness or severe visual impairment. With increased life expectancy, also for leprosy patients, numbers of cataract blind can be expected to further increase.…”
Section: Cataractmentioning
confidence: 99%
“…3,4 The prevalence of blindness due to leprosy has been variously estimated as being 4.7% in India, 9 1.6% in Nigeria, 10 1.3% in China, 11 1.2% in Nepal 12 and 0.6% in Uganda. 13 A selected groups of leprosy affected individuals in hospitals or leprosaria are known to have a high frequency of multiple complications. 9,14,15 …”
Section: Introductionmentioning
confidence: 99%